2015
DOI: 10.5539/gjhs.v8n1p270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Percutaneous Coronary Intervention on Left Ventricular Diastolic Function in Patients With Coronary Artery Disease

Abstract: Background:There is considerable disagreement over the effects of percutaneous coronary intervention (PCI) on left ventricular diastolic function that has necessitated the investigation of diastolic indices. The present study was conducted to evaluate left ventricular diastolic function and its indices, three months after performing the PCI procedure in patients with coronary artery disease (CAD).Methods:In a quasi-experimental clinical trial study (before and after), 51 patients with CAD scheduled for electiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…Moreover, the diagnosis of DHF is more difficult than that of SHF, which easily misses the optimal timing of early treatment for patients with DHF, resulting in poor prognosis or increased risk of death in patients with DHF [ 6 ]. At present, Doppler echocardiography is mostly used to evaluate left ventricular diastolic function for the diagnostic methods of DHF, and the main indicators include mitral annular velocity (Ea) and mitral valve bleeding velocity ( E / A ) [ 7 ]. This method can clearly observe the cardiac structural function and judge the hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the diagnosis of DHF is more difficult than that of SHF, which easily misses the optimal timing of early treatment for patients with DHF, resulting in poor prognosis or increased risk of death in patients with DHF [ 6 ]. At present, Doppler echocardiography is mostly used to evaluate left ventricular diastolic function for the diagnostic methods of DHF, and the main indicators include mitral annular velocity (Ea) and mitral valve bleeding velocity ( E / A ) [ 7 ]. This method can clearly observe the cardiac structural function and judge the hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have done some comparison on LVEF for patients undergoing PCI using echocardiography before, 1 day after and 3-6 months after the procedure. It was found that LVEF improved signi cantly at 1 day and 3-6 months after the procedure, whereas diastolic function improved at 1 day but did not change 3-6 months after the procedure [25]. Other studies have shown that LV diastolic function is altered after PCI [26-28].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have done some comparison on LVEF for patients undergoing PCI using echocardiography before, 1 day after and 3–6 months after the procedure. It was found that LVEF improved significantly at 1 day and 3–6 months after the procedure, whereas diastolic function improved at 1 day but did not change 3–6 months after the procedure [ 25 ]. Other studies have shown that LV diastolic function is altered after PCI [ 26 – 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…And patients with LAD stents were divided into normal and abnormal groups. The T values of both groups were analysed by ROC curves to determine the threshold length of the stent that could cause abnormal T values in LAD implanted stents 3-6 months after the procedure, whereas diastolic function improved at 1 day but did not change 3-6 months after the procedure [25]. Other studies have shown that LV diastolic function is altered after PCI [26][27][28].…”
Section: Discussionmentioning
confidence: 99%